Asupan makan balita pada keluarga perokok dan hubungannya dengan kejadian stunting - Fayasari, Adhila; Istiqomah, Indah Sulistiyani (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Stunting is a major nutritional problem faced by Indonesia because it has a negative impact on various aspects of life. Several factors are the cause of stunting, including the environment and food intake.Objectives: This study aims to analyze the relationship between smoking families, and nutritional intake of children under five with the incidence of stunting in children aged 24-59 months in Sukamaju Baru Village, Depok City.Methods: This study used a cross-sectional design on 75 toddlers and mothers of toddlers in May-June 2022, in the Sukamaju Baru area, Depok City. The data collected in the form of characteristic data, family data of smokers, intake, and anthropometry. Anthropometric data in the form of height as measured by a stadiometer. Intake data were obtained using the 2x24 hour food recall method, not consecutively. Data were analyzed by chi-square test.Results: Stunting was found in 20% of children under five. There was no relationship between smoking families and the incidence of stunting (p 0,027), but there was a significant relationship between energy and protein intake and the incidence of stunting in smoking household (p<0,05). There was no relationship between intake of fat, carbohydrates, and micronutrients with the incidence of stunting in both smoking and non-smoker household (p>0,05).Conclusions: There is a relationship between energy and protein intake with the incidence of stunting in smoking households in Sukamaju Baru, Depok City.